Continuing Professionalisme Development (CPD) sebagai Upaya Mengembangkan Kompetensi Guru PAUD: Continuing Professionalism Development (CPD) as an Effort to Develop PAUD Teacher Competence - Nurhusna Kamil; Erni Munastiwi (Universitas Ngudi Waluyo, 2023)
This article is a descriptive qualitative research with multiple objectives. First, to describe and analyze teacher perceptions about the advantages of the CPD program in developing competence. The second objective is to analyze the teacher's thinking after carrying out CPD activities on competency development which has implications for various advantages during learning for students. Empirical data in the form of interviews with the teacher concerned. The study used a purposive sampling sample with the criteria of teachers who have participated in various CPD activities as an effort to develop pedagogic competence. The data analysis technique used starts from identifying problems, reviewing literature, determining research objectives, collecting data, analyzing data, interpreting data and reporting followed by conclusions. The results of the research from the interviews conducted obtained information that the CPD program is very effective and useful in providing opportunities for teachers to develop teacher competencies so as to provide very qualified accessibility of learning services for students in their growth and development period. ABSTRAK Artikel ini adalah penelitian kualitatif deskriptif dengan tujuan ganda. Yang pertama, untuk mendeskripsikan dan menganalisis persepsi guru tentang keuntungan program CPD dalam mengembangkan kompetensi. Tujuan kedua, untuk menganalisis pemikiran guru setelah melakukan kegiatan CPD terhadap pengembangan kompetensi yang berimplikasi pada berbagai keuntungan selama pembelajaran terhadap siswa. Data empiris berupa hasil wawancara dengan guru yang bersangkutan. Sampel yang digunakan diambil dengan teknik purposive sampling dengan pengklasifikasian guru yang telah mengikuti berbagai kegiatan CPD sebagai upaya mengembangkan kompetensi pedagogik. Teknik analisis data yang digunakan dimulai dari mengidentifikasi masalah, literature review, menentukan tujuan penelitian, mengumpulkan data, menganalisis data, interpretasi data serta pelaporan yang diikuti dengan kesimpulan. Hasil penelitian dari wawancara yang dilakukan didapat informasi bahwa program CPD sangat efektif dan bermanfaat dalam memberikan kesempatan kepada guru dalam mengembangkan kompetensi guru sehingga memberikan aksesibilitas layanan belajar yang sangat mumpuni bagi peserta didik dalam masa pertumbuhan dan perkembangan mereka.